μ-2,3,5,6-Tetrakis(pyridin-2-yl)pyrazine-bis[(2,2′:6′,2′′-terpyridine)ruthenium(II)] tetrakis(hexafluoridophosphate) acetonitrile tetrasolvate - Jude, Hershel (International Union of Crystallography, 2013)
In the title compound [Ru(2)(C(15)H(11)N(3))(2)(C(24)H(16)N(6))](PF(6))(4)·4CH(3)CN, two of the counter-ions and one of the solvent molecules are disordered with occupancies for the major components between 0.57 (2) and 0.64 (1). The structure of the dinuclear tetracation exhibits significant distortion from planarity in the bridging 2,3,5,6-tetrakis(pyridin-2-yl)pyrazine (tppz) ligand, which has a saddle-like geometry with an average dihedral angle of 42.96 (18)° between adjacent pyridine rings. The metal–ligand coordination environment is nearly equivalent for the two Ru(II) atoms, which have a distorted octahedral geometry due to the restricted bite angle [157.57 (13)–159.28 (12)°] of their two mer-arranged tridendate ligands [2,2′:6′,2′′-terpyridine (tpy) and tppz] orthogonal to each other. At the peripheral tpy ligands, the average Ru—N bond distance is 2.072 (4) Å for the outer N atoms trans to each other (N(outer)) and 1.984 (1) Å for the central N atoms (N(central)). At the bridging tppz ligand, the average metal–ligand distances are significantly shorter [2.058 (4) Å for Ru—N(outer) and 1.965 (1) Å for Ru—N(central)] as a result of both the geometric constraints and the stronger π-acceptor ability of the pyrazine-centered bridge. The dihedral angle between the two tpy planes is 27.11 (6)°. The intramolecular linear distance between the two Ru atoms is 6.6102 (7) Å.